Analysis of semiconductor nanowire arrays for photovoltaics - Witzigmann, Bernd; Yu, Shuqing; Kupec, Jan (Proceedings - 2011 International Conference on Electromagnetics in Advanced Applications, ICEAA'11, 2011)
The electro-optical properties of nanowire array solar cells are analyzed with a microscopic simulation model. For the electromagnetic part, the vectorial Helmholtz equation is solved for the three-dimensional structure, and a modal analysis reveals the absorption mechanisms. The electronic part is analyzed with a drift-diffusion approach. It is shown that with a proper design, a III-V nanowire array solar cell can approach the efficiency of a thin-film solar cell, while only a fraction of the active material volume is used. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11